2008
DOI: 10.1055/s-0028-1088344
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobially Active Isoquinoline Alkaloids fromLitsea cubeba

Abstract: Bioassay-guided fractionation of the alkaloidal extract of the aerial part of Litsea cubeba led to the isolation of two new isoquinoline alkaloids, (+)- N-(methoxycarbonyl)-N-norboldine (1) and (+)-isoboldine beta-N-oxide (2), together with 11 known analogues (3-13). Their structures were established by extensive spectroscopic techniques and by comparing spectroscopic data with those in the literature. Compounds 1 and 4 showed antimicrobial activities. This is the first report on the presence of compounds 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Previous phytochemical studies revealed alkaloids, lignans, and volatile oil as its major constituents, and aporphine alkaloids were undoubtedly most representative [16]. These ingredients showed bioactivities on cardiovascular diseases, anticancer, relieving asthma, and significantly attenuating adjuvant arthritis [17][18][19][20]. Our pharmaceutical investigation demonstrated that aporphine alkaloids (compounds 1, 3, 7, and 12) showed significant anti-inflammatory and anti-nociceptive effects in vivo, demonstrated by tests of carrageenan-induced paw edema in rat and xylene-induced ear edema in mouse, and reduce acetic acid-induced writhing as well as the licking time in formalin test and increase reaction latencies in hot plate test (data not shown), suggesting that DCJ alkaloids are responsible for its traditional use of relieving pain and provide scientific evidence for its clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies revealed alkaloids, lignans, and volatile oil as its major constituents, and aporphine alkaloids were undoubtedly most representative [16]. These ingredients showed bioactivities on cardiovascular diseases, anticancer, relieving asthma, and significantly attenuating adjuvant arthritis [17][18][19][20]. Our pharmaceutical investigation demonstrated that aporphine alkaloids (compounds 1, 3, 7, and 12) showed significant anti-inflammatory and anti-nociceptive effects in vivo, demonstrated by tests of carrageenan-induced paw edema in rat and xylene-induced ear edema in mouse, and reduce acetic acid-induced writhing as well as the licking time in formalin test and increase reaction latencies in hot plate test (data not shown), suggesting that DCJ alkaloids are responsible for its traditional use of relieving pain and provide scientific evidence for its clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Pers. (Lauraceae) has long been used as a folk remedy in Traditional Chinese Medicine (TCM) for the treatment of rheumatic diseases (Feng et al 2009). Many pharmacological activities of L. cubeba extract and its compounds have been reported such as anticancer, antibacterial, antioxidant and antiinflammatory immunological activities.…”
Section: Introductionmentioning
confidence: 99%
“…8812, belongs to isoquinoline alkaloids, some of which exhibit antibacterial activity (for example, plant origin products such as berberine, canadaline, canadine, (+)-N-(methoxycarbonyl)-N-norboline). 16,17 Some of them show an activity toward S. aureus, which is analogous to JS-1. Iwasa et al 18 described antimicrobial, antimalarial, cytotoxic and anti-HIV activities of simple, natural and synthetic isoquinoline and benzylisoquinoline alkaloids.…”
Section: Genotoxicitymentioning
confidence: 98%